Pesan Dakwah Dalam Web Series: Analisis Semeotika Roland Barthes Dalam Channel Youtube B3E Production: Story Of Dira Episode 1-9 Edisi 2021 - Rika Handayani; Darul Ilmi (Lembaga Pengembangan Kinerja Dosen, 2023)
Web series is a serial viewing format that is broadcast via web-based internet technology such as YouTube and Vimeo. Web Series have a broadcast concept that is similar to television shows, but Web Series are shorter in duration, have clearer storylines and conflicts and are not long-winded. A strong story makes the audience understand and become more involved in the story, so this media is often used to convey preaching messages. Like one of the Web Series entitled